Psychoanalysis and Developmental Therapy. - Hurry, Anne (Monograph series of the Psychoanalysis Unit of University College, London and the Anna Freud Centre, London, 1998)
The focus of this book is a series of detailed descriptions of clinical work with children. The contributors seek to understand their patients' problems by drawing upon a fundamentally psychoanalytic orientation. Their approach is influenced by recent advances in the understanding of infant development.